2004
DOI: 10.1158/1055-9965.1810.13.11
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk of Leukemia in Older Women

Abstract: Overweight [body mass index (BMI) 25.0-29.9 kg/m2] and obesity (BMI ≥30 kg/m2) are risk factors for several malignancies. The Iowa Women's Health Study was examined to determine whether increased BMI was associated with leukemia development. Over 40,000 Iowa women (ages 55-69 years) completed a self-administered lifestyle and health questionnaire in 1986 that included current height and weight. Two hundred women developed leukemia during the period 1986 to 2001 including 74 acute myelogenous leukemia (AML) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Epidemiological, case control and meta-analysis studies have correlated obesity with poor prognosis for AML. 31 , 32 , 33 , 34 In addition, Finn et al reported an association between obesity and cytogenetic categories. 35 Several studies have considered that obesity might confer poor prognosis in different ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological, case control and meta-analysis studies have correlated obesity with poor prognosis for AML. 31 , 32 , 33 , 34 In addition, Finn et al reported an association between obesity and cytogenetic categories. 35 Several studies have considered that obesity might confer poor prognosis in different ways.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Several studies have considered that obesity might confer poor prognosis in different ways. 3 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 For example, the mean elimination half-life of doxorubicin is longer in obese patients than in normal patients, thus increasing its toxicity to these patients. Adipocytes are also mesenchyme-derived cells and were previously considered to play only a passive “space filling” role in the bone marrow cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has been identified as a significant risk factor for acute myeloid leukemia (AML) development, and case-control studies have demonstrated an approximate 1.5-fold to 2.0-fold increase in adult AML risk associated with obesity, [1][2][3][4][5] particularly in women. [6][7][8] The degree of obesity, its development over the course of life, and, more recently, obesity in adolescents are each associated with an increasing risk of adult AML. 2,9,10 The observation of an increasing incidence of leukemia by birth cohort and by generation supports the hypothesis that adult leukemia risks are appreciably modulated by environmental and lifestyle exposures, 11 thus the obesity-associated lifestyle represents an important and potentially modifiable factor (or behavior) associated with leukemia risk.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been identified as a significant risk factor for acute myeloid leukemia (AML) development, and case–control studies have demonstrated an approximate 1.5‐fold to 2.0‐fold increase in adult AML risk associated with obesity, 1–5 particularly in women 6–8 . The degree of obesity, its development over the course of life, and, more recently, obesity in adolescents are each associated with an increasing risk of adult AML 2,9,10 .…”
Section: Introductionmentioning
confidence: 99%